Klasifikasi Topeng Cirebon menggunakan Metode Convolutional Neural Network - Felix Indra Kurniadi (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Cirebon mask is one of the intangible cultural heritage in Indonesia. It is one of the prominent cultural assets from Cirebon and becoming one of the identity Cirebon culture. However, the current condition people tend to forget the cultural asset and lack of help from the government makes the Cirebon mask become the third-rate assets. Our concern lays on the extinction of this Mask. We want to implement digitation and automatic identification using image processing techniques. In this paper, we applied the Convolutional Neural Network for Cirebon Mask classification.